Pollen limitation and flower abortion in a wind‐pollinated, masting tree. Issue 2 (1st February 2015) - Pearse, Ian S.; Koenig, Walter D.; Funk, Kyle A.; Pesendorfer, Mario B.
Abstract : Pollen limitation is a key assumption of theories that explain mast seeding, which is common among wind‐pollinated and woody plants. In particular, the pollen coupling hypothesis and pollination Moran effect hypothesis assume pollen limitation as a factor that synchronizes seed crops across individuals. The existence of pollen limitation has not, however, been unambiguously demonstrated in wind‐pollinated, masting trees. We conducted a two‐year pollen supplementation experiment on a masting oak species, Quercus lobata . Supplemental pollen increased acorn set in one year but not in the other, supporting the importance of pollen coupling and pollination Moran effect models of mast seeding. We also tracked the fate of female flowers over five years and found that the vast majority of flowers were aborted for reasons unrelated to pollination, even in the presence of excess pollen. Pollen limitation can reduce annual seed set in a wind‐pollinated tree, but factors other than pollen limitation cause the majority of flower abortion.